2010
DOI: 10.1111/j.1548-1387.2010.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex Workers and the Social Context of Workplace Violence in Tijuana, Mexico

Abstract: Gender-based violence in the workplace impacts the physical and emotional wellbeing of sex workers and may lead to other health problems, such as PTSD and depression, drug abuse, and a greater likelihood of sexually transmitted infections. This study examines the social context of workplace violence and risk avoidance in the context of legal regulations meant to reduce harms associated with the industry. Ethnographic research, including 18 months of extended field observations and interviews with 190 female se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…Unlike the women who are providing services within the premises of the bar, the women leaving the premises have no safety net when they encounter a violent client. These findings are similar to other studies that have documented the difference in violence between outdoor and indoor prostitution (Church et al, 2001; Katsulis et al, 2010; Miller, 2002; Raphael & Shapiro, 2004). However, the situation in Mexico is complicated by whether the sex worker is working in a downtown area where prostitution is illegal or in a zona de tolerancia where prostitution is legal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike the women who are providing services within the premises of the bar, the women leaving the premises have no safety net when they encounter a violent client. These findings are similar to other studies that have documented the difference in violence between outdoor and indoor prostitution (Church et al, 2001; Katsulis et al, 2010; Miller, 2002; Raphael & Shapiro, 2004). However, the situation in Mexico is complicated by whether the sex worker is working in a downtown area where prostitution is illegal or in a zona de tolerancia where prostitution is legal.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, research has consistently shown that outdoor versus indoor prostitution is associated with higher levels of violence perpetrated by clients (Church et al, 2001; Katsulis, Lopez, Durfee, & Robillard, 2010; Miller, 2002; Raphael & Shapiro, 2004). For example, Jody Miller (2002) found that sex workers in outdoor venues such as the street had more significant experiences of violence, coercion, and harassment than indoor sex workers in Sri Lanka.…”
mentioning
confidence: 99%
“…By reducing alcohol use and avoiding violent situations, women may have been better able to protect themselves from HIV/STI risk. Katsulis and colleagues (2010) propose that sex workers are constantly negotiating a hierarchy of risk between economic insecurities, substance abuse, sexually transmitted disease, and violence. Our findings suggest that when women are able to better avoid HIV/STI risk and reduce alcohol use, they also improve their ability to mitigate violence.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have associated violence by the police with drug and alcohol use and street prostitution. The convergence of these factors makes women more vulnerable to this type of violence 32,33 .…”
Section: Discussionmentioning
confidence: 99%